ANALYSIS OF ARABIC BANKING TERMINOLOGY ON SHARIA BANK SAVING CUSTOMERS IN SURABAYA - Faruk, Faruk (KONTAN: Jurnal Ekonomi, Manajemen dan Bisnis, 2023)
Since there was a merger one year ago, the world of Islamic banking has a new power to increase the attractiveness of prospective customers to join as customers for both savings and financing. However, if we look back, sometimes there is an obstacle to the Arabic term which they (customers) are ambiguous about, so this is the reason for this research. The purpose of this study is to determine the customer's understanding of Arabic terminology.This research is in the form of a field research with a descriptive qualitative approach, meaning that the research goes down to the field to find, explore and analyze the results of the field. Then analysis is carried out until the validity of the data results in accountable credibility.The results of the research are according to several informants from 3 customers of Islamic banks that Arabic terminology is a way that Islam has regulated the correct banking transactions and further said by other informants that the lack of understanding of Arabic terminology becomes an understanding when becoming a customer and the last is that Arabic terminology becomes an alloy that Islam and banking transactions have clear rules so that they can be safe from ribawi transactions.ABSTRAKSemenjak adanya merger satu tahun yang lalu, dunia perbankan syariah memiliki kekuatan baru untuk meningkatkan daya tarik calon nasabah untuk bergabung menjadi nasabah baik untuk tabungan maupun pembiayaan. Namun, jika kita lihat kembali, terkadang ada kendala pada istilah bahasa Arab yang mereka (nasabah) rancu memahaminya, sehingga hal inilah yang menjadi alasan dilakukannya penelitian ini. Tujuan dari penelitian ini adalah untuk mengetahui pemahaman nasabah terhadap istilah-istilah bahasa Arab Penelitian ini berbentuk penelitian lapangan (field research) dengan pendekatan kualitatif deskriptif, artinya penelitian turun ke lapangan untuk menemukan, menggali dan menganalisis hasil lapangan. Hasil dari penelitian ini adalah menurut beberapa informan dari 3 nasabah bank syariah bahwa terminologi Arab merupakan cara Islam mengatur transaksi perbankan yang benar dan lebih lanjut dikatakan oleh informan lain bahwa kurangnya pemahaman terhadap terminologi Arab menjadi sebuah pemahaman ketika menjadi nasabah dan yang terakhir adalah terminologi Arab menjadi sebuah paduan bahwa Islam dan transaksi perbankan memiliki aturan yang jelas sehingga bisa aman dari transaksi ribawi.